2007
DOI: 10.1080/17477160601095177
|View full text |Cite
|
Sign up to set email alerts
|

What is the best way to measure waist circumference?

Abstract: Waist circumference is a measure of potential value in paediatrics, given its relation to cardiovascular risk in adults. However, three different methods of measurement are currently in use, giving potential for confusion. This study was undertaken to assess consistency across the measures in a population of overweight and normal weight children. We found that when expressed as standard deviation score (SDS) on the British 1990 reference, all three methods correlated highly with body mass index standard deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 8 publications
7
54
0
Order By: Relevance
“…pre-prandial and postprandial period) and it is more practical especially in winter and at busy healthcare sites. In addition, an established standard for the measurement of WC is lacking (31), and the use of WC did not improve the strength of BMI to identify high blood pressure in normal weight children and adolescents (26,32). Therefore, we suggest that NC is a better predictor in normal weight children and adolescents for elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…pre-prandial and postprandial period) and it is more practical especially in winter and at busy healthcare sites. In addition, an established standard for the measurement of WC is lacking (31), and the use of WC did not improve the strength of BMI to identify high blood pressure in normal weight children and adolescents (26,32). Therefore, we suggest that NC is a better predictor in normal weight children and adolescents for elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…BMI (in kg/m 2 ) and FMI (in kg/m 2 ) were calculated. Waist circumference (WC) was measured by using a Seca 200 measuring tape according to standardized instructions (19). To predict change in adiposity from parental feeding, we used raw BMI, WC, and FMI at follow-up with baseline values controlled for.…”
Section: Methodsmentioning
confidence: 99%
“…There are, however, several limitations of WHtR: there have been few longitudinal studies on the relation of childhood WHtR to adult levels; numerous locations have been recommended for the measurement of the waist circumference 15,76 ; and the measurement error for waist circumference is greater than those for weight and height. 14,74 In addition, we have found that WHtR provides relatively little additional information (among all children) on riskfactor levels if BMI is already known.…”
Section: Circumferencesmentioning
confidence: 99%